Electrochemical Detection of Dopamine with Graphene Oxide Carbon Dots Modified Electrodes - Omar Isaac Torres-Soto; Alejandro Vega-Rios; Rocio B. Dominguez; Velia Osuna (Chemosensors)
In this work, the influence of surface functionalization due to synthesis conditions of graphene oxide quantum dots GOQDs was evaluated for dopamine (DA) detection. GOQDs were synthesized using HNO3 (6 M or 8 M) through a liquid-phase oxidation method. The characterization (HRTEM, FTIR, Raman, and XRD) and evaluation by amperometry (AMP) and differential pulse voltammetry (DPV) showed that GOQDs-8 synthesized with higher oxygen content were more sensitive and selective in DA detection than GOQDs-6. The synergistic effects of electrostatic attraction from glassy carbon electrode negatively charged surface, functionalization for inner-sphere mechanism, and edge effect from lower particle size resulted in amplified electrochemical signal achieving detection at nanomolar level using AMP and DPV. When evaluated using AMP, GCE/GOQDs-8 showed a sensitivity of 0.0422 μA μM–1, a limit of detection (LOD) of 17.6 nM, a linear range from 0.1 to 100 μM, and minimal interference for uric acid, levodopa, and acetaminophen. In contrast, using DPV, the GCE/GOQDs-8 exhibited a sensitivity of 0.0616 μA μM–1, a LOD of 506 nM, and a linear range from 0.1–30 μM with remarkable selectivity from all interferent species. The assay of GOQDs-8/GCE sensor in normal human serum proved to be feasible for the practical determination of DA. The recovery obtained was in the range of 94.1 to 112.8% with a relative standard deviation (RSD), n = 3 of less than 3.62%. The oxygen-rich material showed a promising performance that can be further improved with additional nanocarbon or conducting polymers supports.